MEDIA SKRUF UNTUK MENINGKATKAN KEMAMPUAN LITERASI SISWA KELAS RENDAH DI SDK NUABOSI - Tuga, Veronika; Dhiu, Konstantinus Dua; Nafsia, Andi; Ngura, Elisabeth Tantiana (Journal of Practice Learning and Educational Development, 2025)
This research was conducted at SDK Nuabosi with the aim of improving literacy skills, especially in recognizing letters in lower grades by using Skruf as the learning media used. Skruf media is a learning media used to help students recognize letters. This research uses a qualitative method with a qualitative descriptive approach using data collection techniques in the form of observation, interviews, and documentation. Based on the problems experienced by students at SDK Nuabosi, namely low literacy skills caused by the lack of learning media so that students have not been able to recognize letters in this problem the researcher tried to apply learning to recognize letters by applying two indicators, namely mentioning the letters pointed to by the teacher and making scribbles in the form of letters using skruf learning media. In the application of learning to recognize letters in grades 1 and 2 using skruf media, there was an increase where students were able to recognize letters properly and correctly. Based on the problems found in the form of low literacy skills in recognizing letters of grades 1 and 2 at SDK Nuabosi with the solution carried out by researchers using skruf media as the learning media used and there was an increase in literacy in recognizing letters in grades 1 and 2 which was seen from the learning activities to recognize letters carried out using this skruf media, students were able to understand learning to recognize letters with skruf media which uses two indicators used. The role of the learning media used is very useful in helping the learning process where the existence of learning media can help in learning and also foster children's enthusiasm in carrying out the learning process that takes place in class.